Open Research Projects and Public Sociology: Students Communicating Creatively in the Classroom and Beyond - Daniel J. Rose; William V. Taylor (Journal of Public and Professional Sociology)
As teachers, we often deny students the freedom to choose topics of inquiry and methods of communication. We have developed an open research project that challenges students to identify a social problem, gather research, and apply what they have learned by targeting an audience and developing a strategy for effective communication. This assignment centers a “problem-posing” focus that tasks students with confronting relevant issues in their lives and communities. It emphasizes public sociology by shifting the audience for their projects from instructors to classmates, families, communities, and beyond. Students have communicated their work through a variety of mediums, including children’s books, videos, poetry, photojournalism, and other artistic formats. We discuss challenges and strategies involved with this open project. Paradoxically, we have learned from this project that lots of freedom requires lots of structure. We find that for students to create high-quality public sociology, teachers must commit to providing clear expectations, deadlines, communication, and accountability.